Development of Langka Sports Game Application to Increase Physical Activity - Alfin Kukuh Aminuddin; Nasuka; Taufiq Hidayah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Physical activity is something that cannot be separated by human life, especially in the scope of education. Sports become a necessity, in this sport get benefits including to improve, both physical health, mental health (Fauzan, 2021:154) (Fauzan A, 2021: 154)  Currently, humans are spoiled by the existence of technology that is increasingly rapid, the existence of technology that is increasingly developing and sophisticated provides facilities that are easily enjoyed by humans. In study aims to develop an application product that can be used to increase physical activity for students. Referring to the development of Borg and Gall, namely research and development research using learning experts and application media experts, learning experts gave an assessment of 93% and learning media experts gave a score of 100% with very good meaning, worth using. This small group trial used 32 respondents and used 16 questions with 79% results, with a good category, worth using, an increase in pulse rate of 22%. The large group trial used three schools with 87% results, an increase in pulse rate of 24%, the conclusion is that the product can increase physical activity. This developed product will be able to be used easily to assist classroom learning in junior high school.